Intensifying forage legume strata system technology through dairy cattle production - Bollido, Marcos E; Polbos, Teresa B; Bejar, Feleciano R (UI Scholars Hub, 2020)
Intensification of forage legume strata system technology (FLSST) through dairy cattle production was implemented in collaboration with the Department of Agriculture and the local government unit of San Jorge, Samar, Republic of the Philippines. The beneficiaries of the program were selected based on specific criteria and qualifications. Farmers were given training on dairy cattle production, and 10 beneficiaries in five communities received one ready-to-breed cow. Each farmer-beneficiary established a 500 sqm pasture area using FLSST. Abundant grasses and leguminous forages helped improve the health of the cattle. Cattle weighing an average of 150 kg grew to an average weight of 300 kg. The cows gave calves through artificial insemination. Evident impacts were observed as follows: Ground-Level Impact: Participants appreciated the transformation of their idle land into productive land, and farmers were motivated to purchase additional ruminants. Five hectares of idle land was utilized. Deep-Level Impact: Individuals developed a positive attitude toward venturing into ruminant production. Attitudinal transformation among family members was valued by the community, especially by the five farmer-adopters of FLSST. External-Level Impact: Nonparticipants of the project planted leguminous forages in their idle land and developed a positive outlook toward pasture development and dairy cattle production.